GEOSSINTÉTICOS INTELIGENTES EM BARRAGENS: UM PANORAMA DAS INOVAÇÕES NO MONITORAMENTO E PREVENÇÃO DE RISCOS (REMUNOM, 2025)
Geosynthetics have been widely used in engineering, performing essential functions such as reinforcement, filtration, drainage and waterproofing. Since their origin in the 1950s, these materials have evolved significantly, incorporating innovative technologies such as fiber optic sensors that allow real-time monitoring of critical structures such as dams. This review addresses the classification, applications and technological advances of geosynthetics, with an emphasis on their use in dams and the benefits of intelligent solutions compared to traditional monitoring methods. Geosynthetics are classified as geotextiles (woven, non-woven and knitted), geogrids, geomembranes, geotubes and geocomposites, each with specific properties for different applications. They also make it possible to build steeper slopes and stabilize soils with low load-bearing capacity, optimizing costs and efficiency. The integration of fiber optic (FO) sensors into geosynthetics represents a significant advance, allowing early detection of deformations, pressure variations and other structural risks. These “smart geotextiles” offer greater precision and reliability than traditional systems. It is concluded that smart geosynthetics are a promising solution for modern engineering, combining efficiency, sustainability and continuous monitoring. Investments in research and development are essential to expand their application, contributing to safer and more resilient infrastructures. This review paper discusses the applications of geosynthetics in dams, with an emphasis on emerging real-time monitoring technologies. In addition, existing challenges are addressed, such as the need for specific standards for quality control and further research into the durability of geosynthetics in extreme conditions.Keywords: Geosynthetics, dams, intelligent monitoring, fiber optics.